2013
DOI: 10.1007/s10482-013-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

White rot Basidiomycetes isolated from Chiloé National Park in Los Lagos region, Chile

Abstract: Wood decomposition is an important component in forest ecosystems but information about the diversity of fungi causing decay is lacking. This is especially true for the temperate rain forests in Chile. These investigations show results of a biodiversity study of white-rot fungi in wood obtained from Chiloé National Park in Los Lagos region, Chile. Culturing from white-rotted wood followed by sequencing of the complete internal transcribed spacer region of the ribosomal DNA (rDNA) or partial large subunit regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Fungal DNA was isolated and sequenced using the ITS DNA sequence as primers, replicated and sequenced using the Sanger's method. The cultures had a BLAST match of 97 % and more of the sequences in the GenBank database were identified as T. versicolor, C. subvermispora, P. radiata, P. affinis, P. cinerea P. setulosa P. chrysocreas, M. fuscoatra, H. radula, B. adusta, , S. gausapatum and P. sordida, 65 . Compared to Sanger sequencing whole genome sequence studies using next generation sequencers revealed high amount of quality information in the recent years, thus slowly we notice increase in the whole genome sequence studies using NGS methods.…”
Section: Genome and Transcriptome Studies Of Lignocellulose Degradingmentioning
confidence: 99%
“…Fungal DNA was isolated and sequenced using the ITS DNA sequence as primers, replicated and sequenced using the Sanger's method. The cultures had a BLAST match of 97 % and more of the sequences in the GenBank database were identified as T. versicolor, C. subvermispora, P. radiata, P. affinis, P. cinerea P. setulosa P. chrysocreas, M. fuscoatra, H. radula, B. adusta, , S. gausapatum and P. sordida, 65 . Compared to Sanger sequencing whole genome sequence studies using next generation sequencers revealed high amount of quality information in the recent years, thus slowly we notice increase in the whole genome sequence studies using NGS methods.…”
Section: Genome and Transcriptome Studies Of Lignocellulose Degradingmentioning
confidence: 99%
“…Among fungi with wood decay potential, brown-and white-rot fungi (basidiomycetes) provide greater structural damage to the wood cell wall (Ortiz et al 2013). In the present study, R. confertum and P. chrysosporium belong to this class of fungi, therefore causing greater wood deterioration.…”
Section: Isolation and Molecular Identification Of Fungi With Potentimentioning
confidence: 65%
“…This type of lignin removal is preferable for pretreatment of lignocellulosic substrates since it preserves higher amounts of holocellulose. Ligninolytic abilities of S. gausapatum have not been examined before, although the studies of dead wood from which fungi were collected have shown that S. gausapatum causes simultaneous white rotting ( 54 ). As a primary colonizer of oak branches, S. gausapatum is expected to possess good ligninolytic abilities ( 55 ).…”
Section: Resultsmentioning
confidence: 99%